Discrete Mathematics - Proofs

145
Discrete Mathematics Proofs H. Turgut Uyar Ay¸ seg¨ ul Gen¸ cata Yayımlı Emre Harmancı 2001-2013

description

Proof techniques, proof by contradiction, mathematical induction.

Transcript of Discrete Mathematics - Proofs

Page 1: Discrete Mathematics - Proofs

Discrete MathematicsProofs

H. Turgut Uyar Aysegul Gencata Yayımlı Emre Harmancı

2001-2013

Page 2: Discrete Mathematics - Proofs

License

c©2001-2013 T. Uyar, A. Yayımlı, E. Harmancı

You are free:

to Share – to copy, distribute and transmit the work

to Remix – to adapt the work

Under the following conditions:

Attribution – You must attribute the work in the manner specified by the author or licensor (but not in anyway that suggests that they endorse you or your use of the work).

Noncommercial – You may not use this work for commercial purposes.

Share Alike – If you alter, transform, or build upon this work, you may distribute the resulting work onlyunder the same or similar license to this one.

Legal code (the full license):http://creativecommons.org/licenses/by-nc-sa/3.0/

Page 3: Discrete Mathematics - Proofs

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Page 4: Discrete Mathematics - Proofs

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Page 5: Discrete Mathematics - Proofs

Brute Force Method

examining all possible cases one by one

Theorem

Every number from the set {2, 4, 6, . . . , 26} can be writtenas the sum of at most 3 square numbers.

Proof.2 = 1+1 10 = 9+1 20 = 16+44 = 4 12 = 4+4+4 22 = 9+9+46 = 4+1+1 14 = 9+4+1 24 = 16+4+48 = 4+4 16 = 16 26 = 25+1

18 = 9+9

Page 6: Discrete Mathematics - Proofs

Brute Force Method

examining all possible cases one by one

Theorem

Every number from the set {2, 4, 6, . . . , 26} can be writtenas the sum of at most 3 square numbers.

Proof.2 = 1+1 10 = 9+1 20 = 16+44 = 4 12 = 4+4+4 22 = 9+9+46 = 4+1+1 14 = 9+4+1 24 = 16+4+48 = 4+4 16 = 16 26 = 25+1

18 = 9+9

Page 7: Discrete Mathematics - Proofs

Brute Force Method

examining all possible cases one by one

Theorem

Every number from the set {2, 4, 6, . . . , 26} can be writtenas the sum of at most 3 square numbers.

Proof.2 = 1+1 10 = 9+1 20 = 16+44 = 4 12 = 4+4+4 22 = 9+9+46 = 4+1+1 14 = 9+4+1 24 = 16+4+48 = 4+4 16 = 16 26 = 25+1

18 = 9+9

Page 8: Discrete Mathematics - Proofs

Basic Rules

Universal Specification (US)

∀x p(x) ⇒ p(a)

Universal Generalization (UG)

p(a) for an arbitrarily chosen a ⇒ ∀x p(x)

Page 9: Discrete Mathematics - Proofs

Basic Rules

Universal Specification (US)

∀x p(x) ⇒ p(a)

Universal Generalization (UG)

p(a) for an arbitrarily chosen a ⇒ ∀x p(x)

Page 10: Discrete Mathematics - Proofs

Universal Specification Example

Example

All humans are mortal. Socrates is human.Therefore, Socrates is mortal.

U : all humans

p(x): x is mortal

∀x p(x): All humans are mortal.

a: Socrates, a ∈ U : Socrates is human.

therefore, p(a): Socrates is mortal.

Page 11: Discrete Mathematics - Proofs

Universal Specification Example

Example

All humans are mortal. Socrates is human.Therefore, Socrates is mortal.

U : all humans

p(x): x is mortal

∀x p(x): All humans are mortal.

a: Socrates, a ∈ U : Socrates is human.

therefore, p(a): Socrates is mortal.

Page 12: Discrete Mathematics - Proofs

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Page 13: Discrete Mathematics - Proofs

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Page 14: Discrete Mathematics - Proofs

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Page 15: Discrete Mathematics - Proofs

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Page 16: Discrete Mathematics - Proofs

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Page 17: Discrete Mathematics - Proofs

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Page 18: Discrete Mathematics - Proofs

Universal Specification Example

Example

∀x [j(x) ∨ s(x) → ¬p(x)]p(m)

∴ ¬s(m)

1. ∀x [j(x) ∨ s(x) → ¬p(x)] A

2. p(m) A

3. j(m) ∨ s(m) → ¬p(m) US : 1

4. ¬(j(m) ∨ s(m)) MT : 3, 2

5. ¬j(m) ∧ ¬s(m) DM : 4

6. ¬s(m) AndE : 5

Page 19: Discrete Mathematics - Proofs

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Page 20: Discrete Mathematics - Proofs

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Page 21: Discrete Mathematics - Proofs

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Page 22: Discrete Mathematics - Proofs

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Page 23: Discrete Mathematics - Proofs

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Page 24: Discrete Mathematics - Proofs

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Page 25: Discrete Mathematics - Proofs

Universal Generalization Example

Example

∀x [p(x) → q(x)]∀x [q(x) → r(x)]

∴ ∀x [p(x) → r(x)]

1. ∀x [p(x) → q(x)] A

2. p(c) → q(c) US : 1

3. ∀x [q(x) → r(x)] A

4. q(c) → r(c) US : 3

5. p(c) → r(c) HS : 2, 4

6. ∀x [p(x) → r(x)] UG : 5

Page 26: Discrete Mathematics - Proofs

Vacuous Proof

vacuous proof

to prove P ⇒ Q, show that P is false

Page 27: Discrete Mathematics - Proofs

Vacuous Proof Example

Theorem

∀S [∅ ⊆ S ]

Proof.

∅ ⊆ S ⇔ ∀x [x ∈ ∅ → x ∈ S ]∀x [x /∈ ∅]

Page 28: Discrete Mathematics - Proofs

Vacuous Proof Example

Theorem

∀S [∅ ⊆ S ]

Proof.

∅ ⊆ S ⇔ ∀x [x ∈ ∅ → x ∈ S ]∀x [x /∈ ∅]

Page 29: Discrete Mathematics - Proofs

Vacuous Proof Example

Theorem

∀S [∅ ⊆ S ]

Proof.

∅ ⊆ S ⇔ ∀x [x ∈ ∅ → x ∈ S ]∀x [x /∈ ∅]

Page 30: Discrete Mathematics - Proofs

Trivial Proof

trivial proof

to prove P ⇒ Q, show that Q is true

Page 31: Discrete Mathematics - Proofs

Trivial Proof Example

Theorem

∀x ∈ R [x ≥ 0 ⇒ x2 ≥ 0]

Proof.

∀x ∈ R [x2 ≥ 0]

Page 32: Discrete Mathematics - Proofs

Trivial Proof Example

Theorem

∀x ∈ R [x ≥ 0 ⇒ x2 ≥ 0]

Proof.

∀x ∈ R [x2 ≥ 0]

Page 33: Discrete Mathematics - Proofs

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Page 34: Discrete Mathematics - Proofs

Direct Proof

direct proof

to prove P ⇒ Q, show that P ` Q

Page 35: Discrete Mathematics - Proofs

Direct Proof Example

Theorem

∀a ∈ Z [3|(a− 2) ⇒ 3|(a2 − 1)]

Proof.

3|(a− 2) ⇒ ∃k ∈ N [a− 2 = 3k]

⇒ a + 1 = a− 2 + 3 = 3k + 3 = 3(k + 1)

⇒ a2 − 1 = (a + 1)(a− 1) = 3(k + 1)(a− 1)

Page 36: Discrete Mathematics - Proofs

Direct Proof Example

Theorem

∀a ∈ Z [3|(a− 2) ⇒ 3|(a2 − 1)]

Proof.

3|(a− 2) ⇒ ∃k ∈ N [a− 2 = 3k]

⇒ a + 1 = a− 2 + 3 = 3k + 3 = 3(k + 1)

⇒ a2 − 1 = (a + 1)(a− 1) = 3(k + 1)(a− 1)

Page 37: Discrete Mathematics - Proofs

Direct Proof Example

Theorem

∀a ∈ Z [3|(a− 2) ⇒ 3|(a2 − 1)]

Proof.

3|(a− 2) ⇒ ∃k ∈ N [a− 2 = 3k]

⇒ a + 1 = a− 2 + 3 = 3k + 3 = 3(k + 1)

⇒ a2 − 1 = (a + 1)(a− 1) = 3(k + 1)(a− 1)

Page 38: Discrete Mathematics - Proofs

Direct Proof Example

Theorem

∀a ∈ Z [3|(a− 2) ⇒ 3|(a2 − 1)]

Proof.

3|(a− 2) ⇒ ∃k ∈ N [a− 2 = 3k]

⇒ a + 1 = a− 2 + 3 = 3k + 3 = 3(k + 1)

⇒ a2 − 1 = (a + 1)(a− 1) = 3(k + 1)(a− 1)

Page 39: Discrete Mathematics - Proofs

Indirect Proof

indirect proof

to prove P ⇒ Q, show that ¬Q ` ¬P

Page 40: Discrete Mathematics - Proofs

Indirect Proof Example

Theorem

∀x , y ∈ N [x · y > 25 ⇒ (x > 5) ∨ (y > 5)]

Proof.

¬Q ⇔ (0 ≤ x ≤ 5) ∧ (0 ≤ y ≤ 5)

x · y ≤ 5 · 5 = 25

Page 41: Discrete Mathematics - Proofs

Indirect Proof Example

Theorem

∀x , y ∈ N [x · y > 25 ⇒ (x > 5) ∨ (y > 5)]

Proof.

¬Q ⇔ (0 ≤ x ≤ 5) ∧ (0 ≤ y ≤ 5)

x · y ≤ 5 · 5 = 25

Page 42: Discrete Mathematics - Proofs

Indirect Proof Example

Theorem

∀x , y ∈ N [x · y > 25 ⇒ (x > 5) ∨ (y > 5)]

Proof.

¬Q ⇔ (0 ≤ x ≤ 5) ∧ (0 ≤ y ≤ 5)

x · y ≤ 5 · 5 = 25

Page 43: Discrete Mathematics - Proofs

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Page 44: Discrete Mathematics - Proofs

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Page 45: Discrete Mathematics - Proofs

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Page 46: Discrete Mathematics - Proofs

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Page 47: Discrete Mathematics - Proofs

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Page 48: Discrete Mathematics - Proofs

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Page 49: Discrete Mathematics - Proofs

Indirect Proof Example

Theorem

∀a, b ∈ N∃k ∈ N [ab = 2k] ⇒ (∃i ∈ N [a = 2i ]) ∨ (∃j ∈ N [b = 2j ])

Proof.

¬Q ⇔ (¬∃i ∈ N [a = 2i ]) ∧ (¬∃j ∈ N [b = 2j ])

⇒ (∃x ∈ N [a = 2x + 1]) ∧ (∃y ∈ N [b = 2y + 1])

⇒ ab = (2x + 1)(2y + 1)

⇒ ab = 4xy + 2x + 2y + 1

⇒ ab = 2(2xy + x + y) + 1

⇒ ¬(∃k ∈ N [ab = 2k])

Page 50: Discrete Mathematics - Proofs

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Page 51: Discrete Mathematics - Proofs

Proof by Contradiction

proof by contradiction

to prove P, show that ¬P ` Q ∧ ¬Q

Page 52: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Page 53: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Page 54: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Page 55: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Page 56: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Page 57: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Page 58: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

There is no largest prime number.

Proof.

¬P: There is a largest prime number.

Q: The largest prime number is S .

prime numbers: 2, 3, 5, 7, 11, . . . ,S

2 · 3 · 5 · 7 · 11 · · ·S + 1 is not divisibleby a prime number in the range [2,S ]

1 either it is prime itself: ¬Q2 or it is divisible by a prime number greater than S : ¬Q

Page 59: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Page 60: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Page 61: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Page 62: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Page 63: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Page 64: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Page 65: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Page 66: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Page 67: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Page 68: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Page 69: Discrete Mathematics - Proofs

Proof by Contradiction Example

Theorem

¬∃a, b ∈ Z+ [√

2 = ab ]

Proof.

¬P: ∃a, b ∈ Z+ [√

2 = ab ]

Q: gcd(a, b) = 1

⇒ 2 =a2

b2

⇒ a2 = 2b2

⇒ ∃i ∈ Z+ [a2 = 2i ]

⇒ ∃j ∈ Z+ [a = 2j ]

⇒ 4j2 = 2b2

⇒ b2 = 2j2

⇒ ∃k ∈ Z+ [b2 = 2k]

⇒ ∃l ∈ Z+ [b = 2l ]

⇒ gcd(a, b) ≥ 2 : ¬Q

Page 70: Discrete Mathematics - Proofs

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Page 71: Discrete Mathematics - Proofs

Equivalence Proofs

to prove P ⇔ Q, both P ⇒ Q and Q ⇒ P must be proven

a method to prove P1 ⇔ P2 ⇔ · · · ⇔ Pn:P1 ⇒ P2 ⇒ · · · ⇒ Pn ⇒ P1

Page 72: Discrete Mathematics - Proofs

Equivalence Proofs

to prove P ⇔ Q, both P ⇒ Q and Q ⇒ P must be proven

a method to prove P1 ⇔ P2 ⇔ · · · ⇔ Pn:P1 ⇒ P2 ⇒ · · · ⇒ Pn ⇒ P1

Page 73: Discrete Mathematics - Proofs

Equivalence Proof Example

Theorem

a, b, n, q1, r1, q2, r2 ∈ Z+

a = q1 · n + r1b = q2 · n + r2

r1 = r2 ⇔ n|(a− b)

Page 74: Discrete Mathematics - Proofs

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Page 75: Discrete Mathematics - Proofs

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Page 76: Discrete Mathematics - Proofs

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Page 77: Discrete Mathematics - Proofs

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Page 78: Discrete Mathematics - Proofs

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Page 79: Discrete Mathematics - Proofs

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Page 80: Discrete Mathematics - Proofs

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Page 81: Discrete Mathematics - Proofs

Equivalence Proof Example

r1 = r2 ⇒ n|(a− b).

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

r1 = r2 ⇒ r1 − r2 = 0

⇒ a− b = (q1 − q2) · n

n|(a− b) ⇒ r1 = r2.

a− b = (q1 · n + r1)

−(q2 · n + r2)

= (q1 − q2) · n+(r1 − r2)

n|(a− b) ⇒ r1 − r2 = 0

⇒ r1 = r2

Page 82: Discrete Mathematics - Proofs

Equivalence Proof Example

Theorem

A ⊆ B

⇔ A ∪ B = B

⇔ A ∩ B = A

⇔ B ⊆ A

Page 83: Discrete Mathematics - Proofs

Equivalence Proof Example

A ⊆ B ⇒ A ∪ B = B.

A ∪ B = B ⇔ A ∪ B ⊆ B ∧ B ⊆ A ∪ B

B ⊆ A ∪ B x ∈ A ∪ B ⇒ x ∈ A ∨ x ∈ B

A ⊆ B ⇒ x ∈ B

⇒ A ∪ B ⊆ B

Page 84: Discrete Mathematics - Proofs

Equivalence Proof Example

A ⊆ B ⇒ A ∪ B = B.

A ∪ B = B ⇔ A ∪ B ⊆ B ∧ B ⊆ A ∪ B

B ⊆ A ∪ B x ∈ A ∪ B ⇒ x ∈ A ∨ x ∈ B

A ⊆ B ⇒ x ∈ B

⇒ A ∪ B ⊆ B

Page 85: Discrete Mathematics - Proofs

Equivalence Proof Example

A ⊆ B ⇒ A ∪ B = B.

A ∪ B = B ⇔ A ∪ B ⊆ B ∧ B ⊆ A ∪ B

B ⊆ A ∪ B x ∈ A ∪ B ⇒ x ∈ A ∨ x ∈ B

A ⊆ B ⇒ x ∈ B

⇒ A ∪ B ⊆ B

Page 86: Discrete Mathematics - Proofs

Equivalence Proof Example

A ⊆ B ⇒ A ∪ B = B.

A ∪ B = B ⇔ A ∪ B ⊆ B ∧ B ⊆ A ∪ B

B ⊆ A ∪ B x ∈ A ∪ B ⇒ x ∈ A ∨ x ∈ B

A ⊆ B ⇒ x ∈ B

⇒ A ∪ B ⊆ B

Page 87: Discrete Mathematics - Proofs

Equivalence Proof Example

A ⊆ B ⇒ A ∪ B = B.

A ∪ B = B ⇔ A ∪ B ⊆ B ∧ B ⊆ A ∪ B

B ⊆ A ∪ B x ∈ A ∪ B ⇒ x ∈ A ∨ x ∈ B

A ⊆ B ⇒ x ∈ B

⇒ A ∪ B ⊆ B

Page 88: Discrete Mathematics - Proofs

Equivalence Proof Example

A ∪ B = B ⇒ A ∩ B = A.

A ∩ B = A ⇔ A ∩ B ⊆ A ∧ A ⊆ A ∩ B

A ∩ B ⊆ Ay ∈ A ⇒ y ∈ A ∪ B

A ∪ B = B ⇒ y ∈ B

⇒ y ∈ A ∩ B

⇒ A ⊆ A ∩ B

Page 89: Discrete Mathematics - Proofs

Equivalence Proof Example

A ∪ B = B ⇒ A ∩ B = A.

A ∩ B = A ⇔ A ∩ B ⊆ A ∧ A ⊆ A ∩ B

A ∩ B ⊆ Ay ∈ A ⇒ y ∈ A ∪ B

A ∪ B = B ⇒ y ∈ B

⇒ y ∈ A ∩ B

⇒ A ⊆ A ∩ B

Page 90: Discrete Mathematics - Proofs

Equivalence Proof Example

A ∪ B = B ⇒ A ∩ B = A.

A ∩ B = A ⇔ A ∩ B ⊆ A ∧ A ⊆ A ∩ B

A ∩ B ⊆ Ay ∈ A ⇒ y ∈ A ∪ B

A ∪ B = B ⇒ y ∈ B

⇒ y ∈ A ∩ B

⇒ A ⊆ A ∩ B

Page 91: Discrete Mathematics - Proofs

Equivalence Proof Example

A ∪ B = B ⇒ A ∩ B = A.

A ∩ B = A ⇔ A ∩ B ⊆ A ∧ A ⊆ A ∩ B

A ∩ B ⊆ Ay ∈ A ⇒ y ∈ A ∪ B

A ∪ B = B ⇒ y ∈ B

⇒ y ∈ A ∩ B

⇒ A ⊆ A ∩ B

Page 92: Discrete Mathematics - Proofs

Equivalence Proof Example

A ∪ B = B ⇒ A ∩ B = A.

A ∩ B = A ⇔ A ∩ B ⊆ A ∧ A ⊆ A ∩ B

A ∩ B ⊆ Ay ∈ A ⇒ y ∈ A ∪ B

A ∪ B = B ⇒ y ∈ B

⇒ y ∈ A ∩ B

⇒ A ⊆ A ∩ B

Page 93: Discrete Mathematics - Proofs

Equivalence Proof Example

A ∪ B = B ⇒ A ∩ B = A.

A ∩ B = A ⇔ A ∩ B ⊆ A ∧ A ⊆ A ∩ B

A ∩ B ⊆ Ay ∈ A ⇒ y ∈ A ∪ B

A ∪ B = B ⇒ y ∈ B

⇒ y ∈ A ∩ B

⇒ A ⊆ A ∩ B

Page 94: Discrete Mathematics - Proofs

Equivalence Proof Example

A ∩ B = A ⇒ B ⊆ A.

z ∈ B ⇒ z /∈ B

⇒ z /∈ A ∩ B

A ∩ B = A ⇒ z /∈ A

⇒ z ∈ A

⇒ B ⊆ A

Page 95: Discrete Mathematics - Proofs

Equivalence Proof Example

A ∩ B = A ⇒ B ⊆ A.

z ∈ B ⇒ z /∈ B

⇒ z /∈ A ∩ B

A ∩ B = A ⇒ z /∈ A

⇒ z ∈ A

⇒ B ⊆ A

Page 96: Discrete Mathematics - Proofs

Equivalence Proof Example

A ∩ B = A ⇒ B ⊆ A.

z ∈ B ⇒ z /∈ B

⇒ z /∈ A ∩ B

A ∩ B = A ⇒ z /∈ A

⇒ z ∈ A

⇒ B ⊆ A

Page 97: Discrete Mathematics - Proofs

Equivalence Proof Example

A ∩ B = A ⇒ B ⊆ A.

z ∈ B ⇒ z /∈ B

⇒ z /∈ A ∩ B

A ∩ B = A ⇒ z /∈ A

⇒ z ∈ A

⇒ B ⊆ A

Page 98: Discrete Mathematics - Proofs

Equivalence Proof Example

A ∩ B = A ⇒ B ⊆ A.

z ∈ B ⇒ z /∈ B

⇒ z /∈ A ∩ B

A ∩ B = A ⇒ z /∈ A

⇒ z ∈ A

⇒ B ⊆ A

Page 99: Discrete Mathematics - Proofs

Equivalence Proof Example

B ⊆ A ⇒ A ⊆ B.

¬(A ⊆ B) ⇒ ∃w [w ∈ A ∧ w /∈ B]

⇒ ∃w [w /∈ A ∧ w ∈ B]

⇒ ¬(B ⊆ A)

Page 100: Discrete Mathematics - Proofs

Equivalence Proof Example

B ⊆ A ⇒ A ⊆ B.

¬(A ⊆ B) ⇒ ∃w [w ∈ A ∧ w /∈ B]

⇒ ∃w [w /∈ A ∧ w ∈ B]

⇒ ¬(B ⊆ A)

Page 101: Discrete Mathematics - Proofs

Equivalence Proof Example

B ⊆ A ⇒ A ⊆ B.

¬(A ⊆ B) ⇒ ∃w [w ∈ A ∧ w /∈ B]

⇒ ∃w [w /∈ A ∧ w ∈ B]

⇒ ¬(B ⊆ A)

Page 102: Discrete Mathematics - Proofs

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Page 103: Discrete Mathematics - Proofs

Induction

Definition

S(n): a predicate defined on n ∈ Z+

S(n0) ∧ (∀k ≥ n0 [S(k) ⇒ S(k + 1)]) ⇒ ∀n ≥ n0 S(n)

S(n0): base step

∀k ≥ n0 [S(k) ⇒ S(k + 1)]: induction step

Page 104: Discrete Mathematics - Proofs

Induction

Definition

S(n): a predicate defined on n ∈ Z+

S(n0) ∧ (∀k ≥ n0 [S(k) ⇒ S(k + 1)]) ⇒ ∀n ≥ n0 S(n)

S(n0): base step

∀k ≥ n0 [S(k) ⇒ S(k + 1)]: induction step

Page 105: Discrete Mathematics - Proofs

Induction

Definition

S(n): a predicate defined on n ∈ Z+

S(n0) ∧ (∀k ≥ n0 [S(k) ⇒ S(k + 1)]) ⇒ ∀n ≥ n0 S(n)

S(n0): base step

∀k ≥ n0 [S(k) ⇒ S(k + 1)]: induction step

Page 106: Discrete Mathematics - Proofs

Induction

Page 107: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+ [1 + 3 + 5 + · · ·+ (2n − 1) = n2]

Proof.

n = 1: 1 = 12

n = k: assume 1 + 3 + 5 + · · ·+ (2k − 1) = k2

n = k + 1:

1 + 3 + 5 + · · ·+ (2k − 1) + (2k + 1)

= k2 + 2k + 1

= (k + 1)2

Page 108: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+ [1 + 3 + 5 + · · ·+ (2n − 1) = n2]

Proof.

n = 1: 1 = 12

n = k: assume 1 + 3 + 5 + · · ·+ (2k − 1) = k2

n = k + 1:

1 + 3 + 5 + · · ·+ (2k − 1) + (2k + 1)

= k2 + 2k + 1

= (k + 1)2

Page 109: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+ [1 + 3 + 5 + · · ·+ (2n − 1) = n2]

Proof.

n = 1: 1 = 12

n = k: assume 1 + 3 + 5 + · · ·+ (2k − 1) = k2

n = k + 1:

1 + 3 + 5 + · · ·+ (2k − 1) + (2k + 1)

= k2 + 2k + 1

= (k + 1)2

Page 110: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+ [1 + 3 + 5 + · · ·+ (2n − 1) = n2]

Proof.

n = 1: 1 = 12

n = k: assume 1 + 3 + 5 + · · ·+ (2k − 1) = k2

n = k + 1:

1 + 3 + 5 + · · ·+ (2k − 1) + (2k + 1)

= k2 + 2k + 1

= (k + 1)2

Page 111: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+ [1 + 3 + 5 + · · ·+ (2n − 1) = n2]

Proof.

n = 1: 1 = 12

n = k: assume 1 + 3 + 5 + · · ·+ (2k − 1) = k2

n = k + 1:

1 + 3 + 5 + · · ·+ (2k − 1) + (2k + 1)

= k2 + 2k + 1

= (k + 1)2

Page 112: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+ [1 + 3 + 5 + · · ·+ (2n − 1) = n2]

Proof.

n = 1: 1 = 12

n = k: assume 1 + 3 + 5 + · · ·+ (2k − 1) = k2

n = k + 1:

1 + 3 + 5 + · · ·+ (2k − 1) + (2k + 1)

= k2 + 2k + 1

= (k + 1)2

Page 113: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+, n ≥ 4 [2n < n!]

Proof.

n = 4: 24 = 16 < 24 = 4!

n = k: assume 2k < k!

n = k + 1:2k+1 = 2 · 2k < 2 · k! < (k + 1) · k! = (k + 1)!

Page 114: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+, n ≥ 4 [2n < n!]

Proof.

n = 4: 24 = 16 < 24 = 4!

n = k: assume 2k < k!

n = k + 1:2k+1 = 2 · 2k < 2 · k! < (k + 1) · k! = (k + 1)!

Page 115: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+, n ≥ 4 [2n < n!]

Proof.

n = 4: 24 = 16 < 24 = 4!

n = k: assume 2k < k!

n = k + 1:2k+1 = 2 · 2k < 2 · k! < (k + 1) · k! = (k + 1)!

Page 116: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+, n ≥ 4 [2n < n!]

Proof.

n = 4: 24 = 16 < 24 = 4!

n = k: assume 2k < k!

n = k + 1:2k+1 = 2 · 2k < 2 · k! < (k + 1) · k! = (k + 1)!

Page 117: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = k: assume k = 3i + 8j

n = k + 1:

k = 3i + 8j , j > 0 ⇒ k + 1 = k − 8 + 3 · 3⇒ k + 1 = 3(i + 3) + 8(j − 1)k = 3i + 8j , j = 0, i ≥ 5 ⇒ k + 1 = k − 5 · 3 + 2 · 8⇒ k + 1 = 3(i − 5) + 8(j + 2)

Page 118: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = k: assume k = 3i + 8j

n = k + 1:

k = 3i + 8j , j > 0 ⇒ k + 1 = k − 8 + 3 · 3⇒ k + 1 = 3(i + 3) + 8(j − 1)k = 3i + 8j , j = 0, i ≥ 5 ⇒ k + 1 = k − 5 · 3 + 2 · 8⇒ k + 1 = 3(i − 5) + 8(j + 2)

Page 119: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = k: assume k = 3i + 8j

n = k + 1:

k = 3i + 8j , j > 0 ⇒ k + 1 = k − 8 + 3 · 3⇒ k + 1 = 3(i + 3) + 8(j − 1)k = 3i + 8j , j = 0, i ≥ 5 ⇒ k + 1 = k − 5 · 3 + 2 · 8⇒ k + 1 = 3(i − 5) + 8(j + 2)

Page 120: Discrete Mathematics - Proofs

Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = k: assume k = 3i + 8j

n = k + 1:

k = 3i + 8j , j > 0 ⇒ k + 1 = k − 8 + 3 · 3⇒ k + 1 = 3(i + 3) + 8(j − 1)k = 3i + 8j , j = 0, i ≥ 5 ⇒ k + 1 = k − 5 · 3 + 2 · 8⇒ k + 1 = 3(i − 5) + 8(j + 2)

Page 121: Discrete Mathematics - Proofs

Topics

1 Basic TechniquesIntroductionDirect ProofProof by ContradictionEquivalence Proofs

2 InductionIntroductionStrong Induction

Page 122: Discrete Mathematics - Proofs

Strong Induction

Definition

S(n0) ∧ (∀k ≥ n0 [(∀i ≤ k S(i)) ⇒ S(k + 1)]) ⇒ ∀n ≥ n0 S(n)

Page 123: Discrete Mathematics - Proofs

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 2n can be written as the product of prime numbers.

Proof.

n = 2: 2 = 2

assume that the theorem is true for ∀i ≤ k

n = k + 1:

1 if prime: n = n2 if not prime: n = u · v

u < k ∧ v < k ⇒ both u and v can be writtenas the product of prime numbers

Page 124: Discrete Mathematics - Proofs

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 2n can be written as the product of prime numbers.

Proof.

n = 2: 2 = 2

assume that the theorem is true for ∀i ≤ k

n = k + 1:

1 if prime: n = n2 if not prime: n = u · v

u < k ∧ v < k ⇒ both u and v can be writtenas the product of prime numbers

Page 125: Discrete Mathematics - Proofs

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 2n can be written as the product of prime numbers.

Proof.

n = 2: 2 = 2

assume that the theorem is true for ∀i ≤ k

n = k + 1:

1 if prime: n = n2 if not prime: n = u · v

u < k ∧ v < k ⇒ both u and v can be writtenas the product of prime numbers

Page 126: Discrete Mathematics - Proofs

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 2n can be written as the product of prime numbers.

Proof.

n = 2: 2 = 2

assume that the theorem is true for ∀i ≤ k

n = k + 1:

1 if prime: n = n2 if not prime: n = u · v

u < k ∧ v < k ⇒ both u and v can be writtenas the product of prime numbers

Page 127: Discrete Mathematics - Proofs

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 2n can be written as the product of prime numbers.

Proof.

n = 2: 2 = 2

assume that the theorem is true for ∀i ≤ k

n = k + 1:

1 if prime: n = n2 if not prime: n = u · v

u < k ∧ v < k ⇒ both u and v can be writtenas the product of prime numbers

Page 128: Discrete Mathematics - Proofs

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = 15: 15 = 3 · 5 + 8 · 0n = 16: 16 = 3 · 0 + 8 · 2n ≤ k: assume k = 3i + 8j

n = k + 1: k + 1 = (k − 2) + 3

Page 129: Discrete Mathematics - Proofs

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = 15: 15 = 3 · 5 + 8 · 0n = 16: 16 = 3 · 0 + 8 · 2n ≤ k: assume k = 3i + 8j

n = k + 1: k + 1 = (k − 2) + 3

Page 130: Discrete Mathematics - Proofs

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = 15: 15 = 3 · 5 + 8 · 0n = 16: 16 = 3 · 0 + 8 · 2n ≤ k: assume k = 3i + 8j

n = k + 1: k + 1 = (k − 2) + 3

Page 131: Discrete Mathematics - Proofs

Strong Induction Example

Theorem

∀n ∈ Z+, n ≥ 14 ∃i , j ∈ N [n = 3i + 8j ]

Proof.

n = 14: 14 = 3 · 2 + 8 · 1n = 15: 15 = 3 · 5 + 8 · 0n = 16: 16 = 3 · 0 + 8 · 2n ≤ k: assume k = 3i + 8j

n = k + 1: k + 1 = (k − 2) + 3

Page 132: Discrete Mathematics - Proofs

Flawed Induction Example

Theorem

∀n ∈ Z+ [1 + 2 + 3 + · · ·+ n = n2+n+22 ]

invalid base step

n = k: assume 1 + 2 + 3 + · · ·+ k = k2+k+22

n = k + 1:

1 + 2 + 3 + · · ·+ k + (k + 1)

=k2 + k + 2

2+ k + 1 =

k2 + k + 2

2+

2k + 2

2

=k2 + 3k + 4

2=

(k + 1)2 + (k + 1) + 2

2

n = 1: 1 6= 12+1+22 = 2

Page 133: Discrete Mathematics - Proofs

Flawed Induction Example

Theorem

∀n ∈ Z+ [1 + 2 + 3 + · · ·+ n = n2+n+22 ]

invalid base step

n = k: assume 1 + 2 + 3 + · · ·+ k = k2+k+22

n = k + 1:

1 + 2 + 3 + · · ·+ k + (k + 1)

=k2 + k + 2

2+ k + 1 =

k2 + k + 2

2+

2k + 2

2

=k2 + 3k + 4

2=

(k + 1)2 + (k + 1) + 2

2

n = 1: 1 6= 12+1+22 = 2

Page 134: Discrete Mathematics - Proofs

Flawed Induction Example

Theorem

∀n ∈ Z+ [1 + 2 + 3 + · · ·+ n = n2+n+22 ]

invalid base step

n = k: assume 1 + 2 + 3 + · · ·+ k = k2+k+22

n = k + 1:

1 + 2 + 3 + · · ·+ k + (k + 1)

=k2 + k + 2

2+ k + 1 =

k2 + k + 2

2+

2k + 2

2

=k2 + 3k + 4

2=

(k + 1)2 + (k + 1) + 2

2

n = 1: 1 6= 12+1+22 = 2

Page 135: Discrete Mathematics - Proofs

Flawed Induction Example

Theorem

∀n ∈ Z+ [1 + 2 + 3 + · · ·+ n = n2+n+22 ]

invalid base step

n = k: assume 1 + 2 + 3 + · · ·+ k = k2+k+22

n = k + 1:

1 + 2 + 3 + · · ·+ k + (k + 1)

=k2 + k + 2

2+ k + 1 =

k2 + k + 2

2+

2k + 2

2

=k2 + 3k + 4

2=

(k + 1)2 + (k + 1) + 2

2

n = 1: 1 6= 12+1+22 = 2

Page 136: Discrete Mathematics - Proofs

Flawed Induction Example

Theorem

∀n ∈ Z+ [1 + 2 + 3 + · · ·+ n = n2+n+22 ]

invalid base step

n = k: assume 1 + 2 + 3 + · · ·+ k = k2+k+22

n = k + 1:

1 + 2 + 3 + · · ·+ k + (k + 1)

=k2 + k + 2

2+ k + 1 =

k2 + k + 2

2+

2k + 2

2

=k2 + 3k + 4

2=

(k + 1)2 + (k + 1) + 2

2

n = 1: 1 6= 12+1+22 = 2

Page 137: Discrete Mathematics - Proofs

Flawed Induction Example

Theorem

∀n ∈ Z+ [1 + 2 + 3 + · · ·+ n = n2+n+22 ]

invalid base step

n = k: assume 1 + 2 + 3 + · · ·+ k = k2+k+22

n = k + 1:

1 + 2 + 3 + · · ·+ k + (k + 1)

=k2 + k + 2

2+ k + 1 =

k2 + k + 2

2+

2k + 2

2

=k2 + 3k + 4

2=

(k + 1)2 + (k + 1) + 2

2

n = 1: 1 6= 12+1+22 = 2

Page 138: Discrete Mathematics - Proofs

Flawed Induction Example

Page 139: Discrete Mathematics - Proofs

Flawed Induction Example

Theorem

All horses are of the same color.

A(n): All horses in sets of n horses are of the same color.

∀n ∈ N+ A(n)

Page 140: Discrete Mathematics - Proofs

Flawed Induction Example

Theorem

All horses are of the same color.

A(n): All horses in sets of n horses are of the same color.

∀n ∈ N+ A(n)

Page 141: Discrete Mathematics - Proofs

Flawed Induction Example

invalid induction step

n = 1: A(1)All horses in sets of 1 horse are of the same color.

n = k: assume A(k) is trueAll horses in sets of k horses are of the same color.

A(k + 1) = {a1, a2, . . . , ak} ∪ {a2, a3, . . . , ak+1}All horses in set {a1, a2, . . . , ak} are of the same color (a2).All horses in set {a2, a3, . . . , ak+1} are of the same color (a2).

Page 142: Discrete Mathematics - Proofs

Flawed Induction Example

invalid induction step

n = 1: A(1)All horses in sets of 1 horse are of the same color.

n = k: assume A(k) is trueAll horses in sets of k horses are of the same color.

A(k + 1) = {a1, a2, . . . , ak} ∪ {a2, a3, . . . , ak+1}All horses in set {a1, a2, . . . , ak} are of the same color (a2).All horses in set {a2, a3, . . . , ak+1} are of the same color (a2).

Page 143: Discrete Mathematics - Proofs

Flawed Induction Example

invalid induction step

n = 1: A(1)All horses in sets of 1 horse are of the same color.

n = k: assume A(k) is trueAll horses in sets of k horses are of the same color.

A(k + 1) = {a1, a2, . . . , ak} ∪ {a2, a3, . . . , ak+1}All horses in set {a1, a2, . . . , ak} are of the same color (a2).All horses in set {a2, a3, . . . , ak+1} are of the same color (a2).

Page 144: Discrete Mathematics - Proofs

Flawed Induction Examples

Page 145: Discrete Mathematics - Proofs

References

Required Reading: Grimaldi

Chapter 2: Fundamentals of Logic

2.5. Quantifiers, Definitions, and the Proofs of Theorems

Chapter 4: Properties of Integers: Mathematical Induction

4.1. The Well-Ordering Principle: Mathematical Induction

Supplementary Reading: O’Donnell, Hall, Page

Chapter 4: Induction